Pengaruh Servant Leadership, Personality, Dan Karakteristik Pekerjaan Terhadap Organizational Citizenship Behavior Pada PT Pelayaran Agung Samudera - Ningsih, Isromi Dita; Rahayuningsih, Rahayuningsih; Yuliandari, Ni Kadek (Universitas Nusantara PGRI Kediri, 2022)
Human Resource Management is an organizational asset, effectiveness and efficiency can improve the quality ofhuman resources. The presence of the right and quality people that triggers trigger more contributions from employees atwork is Organizational Citizenship Behavior). Research purpose was to determine effect of Servant Leadership, Personalityand Job Characteristics on Organizational Citizenship Behavior at PT Pelayaran Agung Samudera.This research is a quantitative with a random sample technique involving 43 respondents. Analysis of the data usedincludes the Instrument Test, Multiple Linear Regression Test, Hipotesis Test, Coefficient of Determination and ClassicalAssumption Test of Multicollinearity, Heteroscedasticity, and Normality. Based on the results of the SPSS program analysis,it was shown to have a significantly correlated at the level of significant < 0.05 and the value of r arithmetic > r table thendeclared valid in the measurement.